2020
DOI: 10.3342/kjorl-hns.2019.00857
|View full text |Cite
|
Sign up to set email alerts
|

Giant Low-Grade Fibromyxoid Sarcoma in the Neck

Abstract: Low-grade fibromyxoid sarcoma (LGFS) is a soft tissue tumor that rarely occurs in the head and neck region. It occurs mainly in the proximal extremities and the trunk and is prevalent in the young and middle-aged adults. In the present case, LGFS was present at an atypical location and at an unusual age. The treatment of choice for LGFS is radical wide surgical excision with a clear margin. Long-term follow-up is essential for all patients with LGFS, as it has the potential for late recurrence or metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…LGFMSs are aggressive tumors with recurrence, metastasis and death rates of 64%, 45% and 42%, respectively 6 . Nevertheless, treatment options for these tumors remain limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGFMSs are aggressive tumors with recurrence, metastasis and death rates of 64%, 45% and 42%, respectively 6 . Nevertheless, treatment options for these tumors remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals do not respond to the currently available chemotherapy and radiotherapy regimens. Surgical resection and long-term periodical clinical follow-up are still the only treatment modalities available 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…LGFMS is a benign tumor rarely seen in the head and neck region. Despite acting like a benign tumor with a slow course, it can exhibit malignant behaviors such as distant metastasis and local recurrence [8]. In the head and neck region, the maxillary sinus localization of LGFMS is even rarer, and our literature review revealed only five reported cases in total [1,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recurrence after surgery is not the only problem caused by the genetic and histological features of LGFMS. Another factor that makes treatment difficult is the low mitosis rate, which is one of the most characteristic features of the tumor [8,18]. The low mitotic rate and fibrotic background also limit the effectiveness of radiotherapy and chemotherapy, which are highly effective in malignant tumors [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation